Evidence (re)presentation and evidentials in popular and academic history: facts and sources speaking for themselves - Bondi, Marina; Sezzi, Annalisa (Kalbotyra, 2017)
The paper pivots around the different roles of evidentials and the different ways in which evidence is represented in the discourse of popular and academic history, thereby exploring the dynamics of both genres from a discourse analytical perspective. The analysis is based on two corpora of academic and popular articles on history. In particular, it is focused on those lexico-grammatical resources for tracing the speaker’s source and mode of information that constitute the distinguishing features of the two genres. The analysis shows that the high frequency of saw in popular articles refers to the narrative of history, and to the evidence provided by historical characters and sources, rather than by the speaker. The frequency of the attributor according in academic journal articles, on the other hand, clearly qualifies as evidentiality in the narrative of historiography, and acts as a marker of the importance of sources in historical reasoning. The different frequencies thus seem to be related to the different communicative and social functions of the two genres and to be closely connected with the triptych of narratives (Bondi 2015) involved in historical discourse.
Keywords: evidentials; corpus-linguistics; discourse analysis; historical discourse; popular articles; journal articles